Recombinant Myxoma Virus Expressing Walleye Dermal Sarcoma Virus orfC Is Attenuated in Rabbits - Laura V. Ashton; Sandra L. Quackenbush; Jake Castle; Garin Wilson; Jasmine McCoy; Mariah Jordan; Amy L. MacNeill (Viruses, 2020)
The poxvirus, myxoma virus (MYXV) has shown efficacy as an oncolytic virus (OV) in some cancer models. However, MYXV replication within murine cancer models and spontaneous canine sarcomas is short-lived. In mice, successful treatment of tumors requires frequent injections with MYXV. We hypothesize that treatment of cancer with a recombinant MYXV that promotes apoptosis could improve the efficacy of MYXV. The orfC gene of walleye dermal sarcoma virus (WDSV), which induces apoptosis, was recombined into the MYXV genome (MYXVorfC). A marked increase in apoptosis was observed in cells infected with MYXVorfC. To ensure that expression of WDSV orfC by MYXV does not potentiate the pathogenesis of MYXV, we evaluated the effects of MYXVorfC inoculation in the only known host of MYXV, New Zealand white rabbits. Virus dissemination in rabbit tissues was similar for MYXVorfC and MYXV. Virus titers recovered from tissues were lower in MYXVorfC-infected rabbits as compared to MYXV-infected rabbits. Importantly, rabbits infected with MYXVorfC had a delayed onset of clinical signs and a longer median survival time than rabbits infected with MYXV. This study indicates that MYXVorfC is attenuated and suggests that MYXVorfC will be safe to use as an OV therapy in future studies.